Cambodia : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
In this study, the following statistical data are presented in detail: agriculture, livestock, and fishery production, structure of revenue, monetary survey, reserve money, interest rates, central government operations, profile of the commercial bank system, consumer price index, foreign debt, status of state-owned enterprises, proposed privatization standards, gross domestic product by expenditure at current prices, interest rates, budgetary expenditure by ministry, deflators for GDP by sector, sources of broad money growth, deposit money bank's balance sheet, official external assistance to the budget, and so on.